Diversidade beta da comunidade de microfungos assexuais associada à serrapilheira da vegetação ripária no brejo paraibano - Andrade Neto, Antônio Lúcio Barbosa de (2024)
The litter plays a key role in the dynamics of forest ecosystems as it ensures the recycling of nutrients in the environment through their decomposition. Among decomposer microorganisms, asexual microfungi are the most representative. The objective of this study was to investigate the community of asexual microfungi associated with the leaves and twigs of litter present in the riparian zone, during the dry and rainy seasons, in order to verify the influence of the type of substrate and climatic seasonality on the community composition. Two collection expeditions were carried out in October/2021 and February/2022, at Cachoeira da Manga, in Pilões-PB, municipality of Brejo Paraibano. In each expedition, three transects were arranged, equidistant from each other by 100 m, from the river bank towards the interior of the riparian forest. Twenty leaves and 20 branches were collected per transect, totaling 240 substrates throughout the study. The methodology used to detect microfungi was direct observation using the wet chamber technique. A total of 118 microfungal specimens distributed across 58 species and morphospecies were recorded. The most abundant fungi were hyphomycete dematiaceo sp.2, Penicillium sp.1 and Trichoderma sp. with total frequencies of 12.7%, 11% and 5.9%, respectively. Beta diversity analysis revealed that the type of substrate (F= 1.495; p= 0.043) and climatic seasonality (F= 1.799; p= 0.008) had significant influences on the composition of microfungal communities. These variations in communities between different substrates and seasons were driven mainly by an effect of species replacement. The leaves revealed a greater richness of microfungi. Six species were shared between the two substrates, 27 were exclusive to the leaves and 24 to the twigs. Considering climatic seasonality, nine species were shared between the dry and rainy seasons, 21 were exclusive to the dry season and 27 to the rainy season. Similarity percentage analysis revealed that the fungal communities between seasons and substrates were very different from each other, with average dissimilarities of 95.85% and 95.06%, respectively. The microfungi hyphomycete dematiaceo sp.2 and Penicillium sp.1 were the main contributors to the dissimilarities in both factors evaluated. These results highlight the complexity of interactions between microfungi and the terrestrial litter, providing important insights for understanding the ecology of these organisms in forest ecosystems.